Complications of Type 2 Diabetes Mellitus in Children And Adolescents: A Comprehensive International Systematic Review of Spectrum, Burden, and Clinical Implications - Nada Soliman,; Ashraf T. Soliman,; Ahmed Elawwa,; Fawzia Alyafei,; Shayma Ahmed,; Noor Hamed, (Public Health, 2026)
Background: Type 2 diabetes mellitus (T2DM) in children and adolescents represents a rapidly escalating global public-health crisis. Evidence drawn from multiple continents indicates that the disease follows an accelerated, more aggressive course in youth than in adults, with multi-organ complications appearing far earlier than historically anticipated. Objectives: [1] To characterize the prevalence and cumulative incidence of each major complication domain in youth-onset T2DM using data from international cohorts; [2] to compare complication burden across geographic regions and ethnic populations; and [3] to identify modifiable risk factors to guide evidence-based clinical management. Methods: PubMed/MEDLINE, EMBASE, and the Cochrane Library were searched systematically from January 1995 to December 2023. Eligible studies enrolled participants aged ≤18 years with T2DM and reported at least one complication outcome. Thirty-eight studies (N = 42,610 participants across North America, Europe, Asia-Pacific, the Middle East, and Australia) met inclusion criteria. Quality was assessed using the Newcastle-Ottawa Scale (NOS) and the Cochrane RoB-2 tool; pooled estimates were generated using random-effects meta-analysis. Results: Across all regions, hypertension was the most frequent complication (pooled prevalence 42–68%), followed by diabetic kidney disease (DKD; 22–55%), dyslipidemia (38–52%), retinopathy (13–51%), and peripheral neuropathy (12–32%). MASLD/NAFLD affects 40–70% of patients globally. Data from the USA (TODAY, SEARCH), Asia-Pacific (JADE program), Europe (UK and Italian cohorts), multi-national meta-analyses (Nanayakkara et al., 26 countries), and Australia were convergent in demonstrating that each additional year of younger age at diagnosis conferred a 4–5% incremental increase in vascular complication risk. Mental health disorders affected 15–32% of youth with T2DM across all populations studied. Youth-onset T2DM consistently showed higher complication rates than both adult-onset T2DM of equivalent duration and youth-onset T1DM. Conclusions: Youth-onset T2DM imposes an internationally consistent, uniquely aggressive complication phenotype that transcends ethnic and geographic boundaries. Complications worldwide must implement complication screening from the time of diagnosis, integrate psychosocial support, and adopt newer pharmacotherapies with organ-protective properties. Investment in equitable, globally applicable, pediatric-specific protocols is urgently needed